A comparative study of NiCo2O4 catalyst supported on Ni foam and from solution residuals fabricated by a hydrothermal approach for electrochemical oxygen evolution reaction. Issue 93 (7th November 2018) - Yang, Liting; Zhang, Baogang; Fang, Bo; Feng, Ligang
Abstract : Residuals should be given more attention when catalyst is prepared using the hydrothermal fabrication approach. Abstract : Residuals have rarely been granted attention when employing a hydrothermal approach to prepare binder-free supported catalysts. Using Ni foam supported NiCo2 O4 catalyst for oxygen evolution reaction as an example, it was found that the catalytic activity of NiCo2 O4 from the residuals loaded on glass carbon is comparable to Ni foam supported NiCo2 O4, while the specific activity and turnover frequency value of the former catalyst are many times higher than that of the supported catalyst. In view of sustainability and green development, residuals should be given more attention when catalyst is prepared using the hydrothermal fabrication approach.